COMPARISON OF THE SUPREME COURTS OF INDONESIA AND MALAYSIA REGARDING THEIR DUTIES AND AUTHORITIES - Lukita, Muhammad Gani; Valentina, Lotua (EKSEKUSI, 2025)
Indonesia and Malaysia are two countries with two different laws where Indonesia is a country that applies Civil Law and malaysia with Common Law. The difference between this two systems lays with how they run the judicial systems that also includes what task and leverage of the supreme court of Indonesia and Malaysia. The problem statement in this journal will inquire about the duty and leverage of the Supreme Court of Indonesia. The research method that is going to be use in these journal will use normative method where the author going to analyze on the norms that applied in the country. The research method that is going to be use in this journal include issues, rules, application, and conclusion or (IRAC). Writer conclude that the Supreme Court holds major influence in the judicial system in Indonesia and Malaysia.